Promoter hypermethylation along with LOH, but not mutation, contributes to inactivation of DLC‐1 in nasopharyngeal carcinoma. Issue 11 (12th June 2013) - Feng, Xiangling; Ren, Caiping; Zhou, Wen; Liu, Weidong; Zeng, Liang; Li, Guifei; Wang, Lei; Li, Min; Zhu, Bin; Yao, Kaitai; Jiang, Xingjun
Abstract Previous studies have shown that promoter hypermethylation plays a key role in DLC‐1 inactivation in nasopharyngeal carcinoma (NPC). However, DLC‐1 mutation in NPC has not been reported, and there remain some discrepancies in methods and results between different groups. Here, we examined the mRNA and protein expression of DLC‐1 in chronic nasopharyngitis (CN) and NPC tissues by reverse transcription‐polymerase chain reaction/qPCR and immunohistochemistry, respectively. DLC‐1 mRNA was undetectable in all the seven widely used NPC cell lines and absent or significantly down‐regulated in 70% of NPC tissues. DLC‐1 protein level was reduced in 74.3% of NPCs when compared with CN tissues, and significantly lower in NPC samples at advanced clinical stages than that at early stages. Then, we purified the same batch of specimens by microdissection and analyzed the possible mechanisms of DLC‐1 downregulation with mutation and allelic loss analysis, methylation‐specific PCR and bisulfite genomic sequencing. Only one mutation was detected at codon 693 of exon 8 in 3.3% of NPCs and five single nucleotide polymorphisms (SNPs) were identified. Loss of DLC‐1 was detected in 23.3% of NPC tissues. The 100% of NPC cell lines, 80% of primary NPC and 22.2% of CN tissues showed methylation in DLC‐1 promoter, while DLC‐1 expression was recovered in seven NPC cell lines after 5‐aza‐dC treatment. Patched methylation assay confirmed that promoter methylation could repress DLC‐1 expression. This report demonstrates that DLC‐1 is negatively associated with NPC carcinogenesis, and promoter hypermethylation along with loss of heterozygosity, but not mutation, contributes to inactivation of DLC‐1 in NPC. © 2013 Wiley Periodicals, Inc.